2015
DOI: 10.4236/ns.2015.77040
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Microalgae <i>Monoraphidium</i> sp., in the Plant Pilot the Grand Valle Bio Energy, for Biodiesel Production

Abstract: At present, Brazil imports approximately 11 billion liters/year of diesel. With the interruption of the works in the new Petrobras refineries, the projection is that by 2025 this volume will increase to 24.2 billion liters of diesel/year. In this sense, the biodiesel factory Grand Valle Bio Energy Ltda., located in the state of Rio de Janeiro, in conjunction with the FAPERJ makes some investments in technology development for the cultivation and use of microalgae as an alternative raw material in the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
2
6
0
4
Order By: Relevance
“…The protein and carbohydrate contents obtained in this study correspond to the values reported in the literature for this microalgae species that are between 28% -45% of proteins and 17% -35% of carbohydrates [23]. According to these The content of biodiesel convertible lipids (LCB) was 8.36%, a value considered low when compared to other studies that appear in the literature that report values between 15% and 20% [30].…”
Section: Resultssupporting
confidence: 82%
“…The protein and carbohydrate contents obtained in this study correspond to the values reported in the literature for this microalgae species that are between 28% -45% of proteins and 17% -35% of carbohydrates [23]. According to these The content of biodiesel convertible lipids (LCB) was 8.36%, a value considered low when compared to other studies that appear in the literature that report values between 15% and 20% [30].…”
Section: Resultssupporting
confidence: 82%
“…The EAAI was above 0.9 in our three media, which suggests that SDEC-17 could produce the best protein based on a FAO/WHO [32] standard and become a good protein source for animal food. In contrast to protein, cultivation with CW and CW 0 BG11 cut down the carbohydrate content in algae cells slightly, lower than the general value (17-25%) summarized by Díaz et al [33]. However, regarding the sum proportion of protein and carbohydrate, the media CW (59%) exhibited superiority over BG11 media (51%), indicating that cultivation of SDEC-17 with CW might become a very economical way to support feedstock supply for fermentation of bioethanol compared with the cultivation in BG11.…”
Section: Protein and Carbohydrate Accumulationmentioning
confidence: 57%
“…These data are consistent with the typical protein content in the biomass Monoraphidium sp. (28-45%) reported by Díaz et al [33]. Cultivating SDEC-17 in CW improved the protein content a lot, making it even higher than that in other native species [7,31] and S. subsalsa in CW [9].…”
Section: Protein and Carbohydrate Accumulationmentioning
confidence: 64%
See 1 more Smart Citation
“…This company developed the cultivation of the microalga Monoraphidium sp. in pilot-scale photobioreactors [181].…”
Section: Microalgae Biorefinery As An Integral Systemmentioning
confidence: 99%